Effect of gender on the adaptation of arm coordination in front crawl - Seifert, L.; Boulesteix, L.; Chollet, D. (International Journal of Sports Medicine, 2004)
The aim of this study was to compare the arm coordination of 14 elite men swimmers and 10 elite women swimmers at eight different velocities, from the usual 3000 m velocity to their maximal velocity (Vmax). Each stroke phase was identified by video analysis and the Index of Coordination (IdC) was established. Three modes of coordination have been identified: catch-up (IdC < 0); opposition (IdC = 0); and superposition (IdC > 0). This study shows that at a greater individually imposed swim pace (ISP) elite men spontaneously adapt by opposing their arms during sprint time (IdC = +2.57 ± 6 % at Vmax), whereas elite women (IdC = -3.88 ± 6.1 % at Vmax) adapt more slowly, remaining in catch-up coordination. Elite men favoured the increase of propulsive actions by increasing the propulsive phases (pull and push phases) and decreasing the entry + catch phase, even if the recovery phase increased. Elite women generated less propulsive actions during sprint, i. e. shorter push and pull phases and a longer entry + catch phase. The biomechanical constraints (effective velocity: EV) could explain that men switched coordination at high velocity (sprint), whilst the differences between men and women at a similar EV related more to their motor organisation than to biomechanical constraints. Anthropometric data could partially explain this difference between genders. Height (171.6 ± 5.8 cm vs. 185.5 ± 4.2 cm) and arm span (177.12 ± 6.24 cm vs. 192.75 ± 1.83 cm) were smaller in women than in men. The women catch-up coordination was not a "worse coordination" when compared with that of men, but it reflected a different motor organisation resulting from different anthropometric properties and swimming technique. Therefore, catch-up coordination could be an individual response to different constraints.